1999
DOI: 10.1093/emboj/18.18.4935
|View full text |Cite
|
Sign up to set email alerts
|

GTP hydrolysis by arf-1 mediates sorting and concentration of Golgi resident enzymes into functional COP I vesicles

Abstract: Upon addition of GTPγS to in vitro budding reactions, COP I vesicles form but retain their coat, making them easy to isolate and analyze. We have developed an in vitro budding assay that reconstitutes the formation of COP I-derived vesicles under conditions where GTP hydrolysis can occur. Once formed, vesicles are uncoated and appear functional as they fuse readily with acceptor membranes. Electron microscopy shows a homogeneous population of uncoated vesicles that contain the medial/trans Golgi enzyme α1,2-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
193
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(214 citation statements)
references
References 68 publications
(107 reference statements)
19
193
2
Order By: Relevance
“…41,66,67 Previously, the Golgi dispersion has been explained as inhibition of vesicle formation. However, given our results that (1) ArfGAP1 overexpression leads to the accumulation of vesicles and (2) 19,20,22,23 In vitro, we found that both Arf1•GTPgS and Arf1•GTP can induce membrane deformation with cargo, coatomer, and ArfGAP1 in LUVs. However, LUVs were more extensively tubulated and deformed with Arf1•GTP than Arf1•GTPgS ( Fig.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…41,66,67 Previously, the Golgi dispersion has been explained as inhibition of vesicle formation. However, given our results that (1) ArfGAP1 overexpression leads to the accumulation of vesicles and (2) 19,20,22,23 In vitro, we found that both Arf1•GTPgS and Arf1•GTP can induce membrane deformation with cargo, coatomer, and ArfGAP1 in LUVs. However, LUVs were more extensively tubulated and deformed with Arf1•GTP than Arf1•GTPgS ( Fig.…”
Section: Discussionmentioning
confidence: 48%
“…[19][20][21][22][23] The finding that interfering with GTP hydrolysis by Arf resulted in production of transport vesicles that lacked cargo was the basis for the suggestion that GTP hydrolysis by Arf1 facilitates cargo sorting into coated vesicles. [23][24][25] The model for Arf-dependent COPI vesicle formation was modified to accommodate the result.…”
Section: Introductionmentioning
confidence: 99%
“…COP I coat proteins mediate an essential and conserved retrieval pathway that continually recycles several classes of proteins, and lipids, from the cis-Golgi back to the endoplasmic reticulum (ER) Gaynor et al, 1998;Lanoix et al, 1999). Additionally, the COP I coat functions in retrograde transport and perhaps also in anterograde transport, within the Golgi complex (Orci et al, 1997;Pelham and Rothman, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This recycling helps to ensure that steady-state distributions of resident proteins are maintained within the pathway at the same time as keeping a lipid balance. Besides intra-Golgi recycling between cisternae (Hoe et al, 1995;Love et al, 1998;Lanoix et al, 1999;Lin et al, 1999), Golgi glycosylation enzymes also can recycle directly to the endoplasmic reticulum (ER). It is estimated that at least 5% of Golgi resident enzymes reside in the ER, at steady state (Pelletier et al, 2000).…”
mentioning
confidence: 99%